Analyse des styles ou stratégies d'enseignants dans l'apprentissage grammatical - Philippe Clauzard (Nantes Université, 2014)
When approaching teachers' job, it is observed what is specific to the work of teachers during grammar lessons in elementary school. A wildcard can model the actual situation of class work with the updating of teaching activity organizers. To this is added a generic singular dimension that establishes a personal response to a professional problem consisting in "how to teach school grammar"? Detailed observation of interactions based coactivity class teacher-student identifies personal ways of acting, enlist students in the academic task, support their learning. This is done on the basis of adjustments of situations, representations about the area of pupils'close development, personal designs on the study of language. These strategies revealed by the researcher allow to understand a style of teaching grammar.